2010
DOI: 10.1111/j.1651-2227.2010.01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol in early infancy: the risk of childhood allergy and asthma

Abstract: Paracetamol exposure in pregnancy was associated with allergic rhinitis, but not with asthma or allergic sensitization at 10 years of age. Paracetamol used until 6 months of age was associated with allergic sensitization and having a history of asthma in girls at 10 years of age, even considering concomitant airway infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 27 publications
2
52
1
1
Order By: Relevance
“…When they controlled for documented early respiratory infections, or restricted the analysis to non-respiratory indications for acetaminophen use, there was no evidence of increased odds of current asthma at age 6-7 years, suggesting that apparent links with infant acetaminophen use are confounded by febrile respiratory infections associated with wheezing which persists. Another birth cohort similarly found evidence to suggest that the apparent association between infant acetaminophen use and childhood asthma was confounded by respiratory infections, 39 although the Norwegian study did not, 37 and nor did the study from Ethiopia. 36 Therefore, despite some current evidence that suggests links between acetaminophen intake and contemporaneous asthma symptoms in children, there remains considerable doubt about the robustness of reported associations between use in early infancy and the development of asthma in later childhood.…”
Section: Acetaminophen In Children and Asthmamentioning
confidence: 95%
See 2 more Smart Citations
“…When they controlled for documented early respiratory infections, or restricted the analysis to non-respiratory indications for acetaminophen use, there was no evidence of increased odds of current asthma at age 6-7 years, suggesting that apparent links with infant acetaminophen use are confounded by febrile respiratory infections associated with wheezing which persists. Another birth cohort similarly found evidence to suggest that the apparent association between infant acetaminophen use and childhood asthma was confounded by respiratory infections, 39 although the Norwegian study did not, 37 and nor did the study from Ethiopia. 36 Therefore, despite some current evidence that suggests links between acetaminophen intake and contemporaneous asthma symptoms in children, there remains considerable doubt about the robustness of reported associations between use in early infancy and the development of asthma in later childhood.…”
Section: Acetaminophen In Children and Asthmamentioning
confidence: 95%
“…In addition to studies that have considered symptomatic or reported doctor-diagnosed asthma as outcomes, which are open to misclassification and reporting bias, there have been reports of associations of acetaminophen exposure during pregnancy with measured asthma-related phenotypes, including lung function, bronchial responsiveness, exhaled nitric oxide (FeNO) measurements, atopy and total IgE. In Bakkeheim and others' study of a prospective birth cohort in Oslo, 56 they reported secondary outcomes that included associations with high FeNO and bronchial hyperresponsiveness at age 10 years, although the latter attenuated substantially on adjustment for confounders. Acetaminophen use in the third trimester of pregnancy was also associated with bronchial responsiveness measured in infants at 1 month of age in the Copenhagen Prospective Study of Asthma in Childhood (COPSAC), a study based on families at high risk for asthma.…”
Section: Acetaminophen In Pregnancy and Asthma In The Offspringmentioning
confidence: 98%
See 1 more Smart Citation
“…28 However, in another study, the association between asthma and paracetamol use persisted even after adjusting for respiratory infections. 29 A cohort study that evaluated the use of paracetamol during pregnancy observed that the use of this drug was associated with the presence of asthma at age five and the risk was higher in those who had a greater number of days of consumption, suggesting a possible dose-dependent association. 30 Therefore, the association between paracetamol and wheezing/asthma may simply reflect a reverse causality, i.e.…”
Section: Variablesmentioning
confidence: 98%
“…Although hypersensitivity to paracetamol is considered to be a rare occurrence, reactions may be represented by urticaria, angioedema, dyspnea and rhinitis or very rarely, an anaphylactic reaction (Boussetta et al, 2005;Couto and Gaspar, 2012). There have also been several studies carried out which link the use of paracetamol in early infancy to the later onset of asthma and allergic rhinitis (Bakkeheim et al, 2011). In the United Kingdom, 60 mg of paracetamol administered 4 times per day is the recommended optimum dose for a 3-6 month infant.…”
Section: Introductionmentioning
confidence: 99%